Identification of absorbed constituents and evaluation of the pharmacokinetics of main compounds after oral administration of yindanxinnaotong by UPLC-Q-TOF-MS and UPLC-QqQ-MS. Issue 28 (26th April 2018) - Gong, Leilei; Xu, Haiyu; Yuan, Huijun; Wang, Lan; Yin, Xiaojie; Fan, Moqi; Cheng, Long; Ma, Xiaojing; Liang, Rixin; Yang, Hongjun
Abstract : Yindanxinnaotong capsule (YDXNT), a traditional Chinese formula, has been used to treat cardio-cerebrovascular diseases for several decades. Abstract : Yindanxinnaotong capsule (YDXNT), a traditional Chinese formula, has been used to treat cardio-cerebrovascular diseases for several decades. Previous research has focused on evaluating the pharmacological properties and main compounds of YDXNT in vitro and in vivo . However, the multiple bioactive compounds in vivo remain poorly understood. In the present research, an integrative strategy using UPLC-Q-TOF-MS combined with UPLC-QqQ-MS was employed to detect the absorbed constituents and investigate the pharmacokinetics of main compounds in the plasma after oral administration of YDXNT. UPLC-Q-TOF-MS was developed to detect the absorbed constituents and their metabolites in the plasma after oral administration in rats. A total of 52 constituents, including 44 prototype compounds and 8 metabolites, were identified or tentatively characterized. Then, nine main compounds (quercetin, isorhamnetin, kaempferol, ginkgolide A, ginkgolide B, ginkgolide C, bilobalide, tanshinone IIA, and salvianolic acid B) were chosen to further investigate the pharmacokinetic behavior of YDXNT using UPLC-QqQ-MS. The concentration of nine main constituents were in the range of 27.85–76.54 ng mL −1 . This research provides a systematic approach for rapid qualitative analysis of absorbed constituents and for evaluating the pharmacokinetics of the main ingredients of YDXNT following its oral administration. More importantly, this work provides key information on the identification of bioactive compounds and the clarification of their action mechanisms, as well as on the pharmacological actions of YDXNT.